Association of sleep problems with suicidal behaviors and healthcare utilization in adults with chronic diseases: the role of mental illness - Chen Wen; Zheng Wei; Nasr Chalghaf; Woldegebriel Assefa Woldegerima; Jianhong Wu; Nicola Luigi Bragazzi; Sergio Garbarino (Annals of General Psychiatry)
Abstract Objectives This study aimed to investigate the association between sleep problems and suicidal behaviors as well as healthcare utilization in Canadian adults with chronic diseases, while also examining the mediating role of mental illness. Methods Data were drawn from the 2015–16 cycle of the Canadian Community Health Survey, specifically from Ontario, Manitoba, and Saskatchewan — the provinces that included the optional sleep module. A total of 22,700 participants aged ≥ 18 years and diagnosed with at least one chronic disease were included in the analysis. Sleep problems were defined as extreme sleep durations (either < 5 or ≥ 10 h) and insomnia. Mental illness was classified as a self-reported mood or anxiety disorder. Results Participants with extreme sleep durations (compared to 7 to < 8 h) and those with insomnia (compared to no insomnia) showed a higher prevalence of suicidal ideation, suicidal plans, and increased healthcare utilization. After adjusting for multiple covariates, both extreme sleep durations and insomnia remained significantly associated with increased odds of suicidal ideation, suicidal plans, and healthcare utilization. Mediation analyses indicated that mental illness partially mediated these associations. Conclusions Both extreme sleep durations and insomnia were independently associated with higher odds of suicidal behaviors and increased healthcare utilization in adults with chronic diseases, with mental illness playing a partial mediating role in these relationships.